Challenges and Strategies of Low‐Cost Aluminum Anodes for High‐Performance Al‐Based Batteries. Issue 2 (19th October 2021) - Jiang, Min; Fu, Chaopeng; Meng, Pengyu; Ren, Jianming; Wang, Jing; Bu, Junfu; Dong, Anping; Zhang, Jiao; Xiao, Wei; Sun, Baode
Abstract: The ever‐growing market of electric vehicles and the upcoming grid‐scale storage systems have stimulated the fast growth of renewable energy storage technologies. Aluminum‐based batteries are considered one of the most promising alternatives to complement or possibly replace the current lithium‐ion batteries owing to their high specific capacity, good safety, low cost, light weight, and abundant reserves of Al. However, the anode problems in primary and secondary Al batteries, such as, self‐corrosion, passive film, and volume expansion, severely limit the batteries' practical performance, thus hindering their commercialization. Herein, an overview of the currently emerged Al‐based batteries is provided, that primarily focus on the recent research progress for Al anodes in both primary and rechargeable systems. The anode reaction mechanisms and problems in various Al‐based batteries are discussed, and various strategies to overcome the challenges of Al anodes, including surface oxidation, self‐corrosion, volume expansion, and dendrite growth, are systematically summarized. Finally, future research perspectives toward advanced Al batteries with higher performance and better safety are presented. Abstract : Al, with the features of high specific capacity, low‐cost, and abundant reserves, is promising for energy storage. The recent progress of Al anodes for various Al‐based batteries is summarized. The challenges of Al anodes leading to a mismatch between theoretical and practical performance are discussed. Comprehensive strategies for Al anodes to boost the electrochemical performance are presented.